Stabilization analysis of impulsive state-dependent neural networks with nonlinear disturbance: A quantization approach - Hong, Yaxian; Bin, Honghua; Huang, Zhenkun (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the problem of feedback stabilization for a class of impulsive state-dependent neural networks (ISDNNs) with nonlinear disturbance inputs via quantized input signals is discussed. By constructing quasi-invariant sets and attracting sets for ISDNNs, we design a quantized controller with adjustable parameters. In combination with a suitable ISS-Lyapunov functional and a hybrid quantized control strategy, we propose novel criteria on input-to-state stability and global asymptotical stability for ISDNNs. Our results complement the existing ones. Numerical simulations are reported to substantiate the theoretical results and effectiveness of the proposed strategy.
Keywords: state-dependent neural networks; quantized input; stabilization